2022
DOI: 10.1071/py21081
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to nurse-led advance care planning and palliative care practice change in primary healthcare: a qualitative study

Abstract: Primary care settings are ideal for initiating advance care planning (ACP) conversations and assessing palliative and supportive care needs. However, time constraints and a lack of confidence to sensitively and efficiently initiate such discussions are noted barriers. The Advance Project implemented a national multicomponent training package to support Australian general practice nurses (GPNs) to work with GPs to initiate ACP and palliative care conversations in their practice. This paper reports on semistruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Professionals in this study argued that ACP implementation could be improved with facilitators who could oversee implementation, and coordinate training and support, similar to findings in other studies [ 29 , 30 ]. This also aligns with the integrated framework for Promoting Action on Research Implementation in Health Services, i-PARIHS, in which competent facilitation is seen as the active agent for successful implementation of innovation into working healthcare practice [ 31 ].…”
Section: Discussionsupporting
confidence: 81%
“…Professionals in this study argued that ACP implementation could be improved with facilitators who could oversee implementation, and coordinate training and support, similar to findings in other studies [ 29 , 30 ]. This also aligns with the integrated framework for Promoting Action on Research Implementation in Health Services, i-PARIHS, in which competent facilitation is seen as the active agent for successful implementation of innovation into working healthcare practice [ 31 ].…”
Section: Discussionsupporting
confidence: 81%
“…The included studies used length of residence as an underpinning concept relating to healthcare access. The review demonstrated that access barriers were experienced despite the number of years settled in the host country [ 52 ]. Such experiences in accessing and utilising mainstream healthcare points towards ongoing systemic factors related to discrimination and marginalisation of migrants and refugees, where these groups are inequitably positioned within society in Aotearoa regardless of the years they have been resettled [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%